Establishing a Crown Agency Amid Multiple Service Providers: Self-Directed Personal Support Services Ontario (SDPSSO) - Lisette Dansereau; Mary Jean Hande; Christine Kelly (McMaster University Library Press, 2019)
Directly funded (DF) home care is a policy mechanism where individuals are given funds to arrange their own services by hiring people in their communities or by subcontracting to service provider organizations. In 2017, the Ontario Ministry of Health and Long-Term Care briefly established a crown agency called Self-Directed Personal Support Services Ontario (SDPSSO). The stated goal of the SDPSSO was to create a DF home care program to serve older people, expanding an existing Ontario program serving a small number of younger adults with disabilities. The development of SDPSSO was influenced by the then health minister's ideological belief, pressure to reform home care from multiple stakeholders, and positive (although sparse) international evidence of the efficacy of DF home care among older adults. Reaction to the policy shift included a judicial injunction brought forward by a coalition group of home care service providers, halting implementation. A SWOT analysis shows that the SDPSSO provided as many threats and unknowns as there were possible benefits. A change in provincial government resulted in the dissolution of the SDPSSO in 2018 and the introduction of a family-managed program that continues to exclude older people. It is unclear what future changes may be in store for home care in Ontario.